Progressive Muscle Relaxation Training untuk Mengurangi Kecemasan pada Ibu Hamil Pra-Melahirkan - Sri Ayatina Hayati; Aminah Aminah; Nurul Auliah; Endang Pratiwi (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2020)
This study aims to provide training to pre-natal pregnant women by using progressive muscle relaxation training to reduce anxiety in pre-natal pregnant women at the 9 November Banjarmasin Health Center. The objectives of this training include: (1) Providing information about the impact, procedures and elements that pre-delivery pregnant women must know at the 9 November Banjarmasin health center in preparation for the Progressive Muscle Relaxation Training. (2) Providing Progressive Muscle Relaxation Training skills training for pregnant women at the 9 November Banjarmasin health center so that they can apply the movements of the Progressive Muscle Relaxation Training when experiencing pre-birth anxiety. Methods in carrying out activities include the following: (1) Lecture: (2) Training: and (3) Evaluation. The target population in this activity was pregnant women with their first pregnancy at the health center on November 9, Banjarmasin. Judging from the level of effectiveness, progressive muscle relaxation training is effective in reducing anxiety in pre-natal pregnant women at the 9 November Banjarmasin Health Center;  Keywords: Progressive Muscle Relaxation Training, Anxiety, Pregnant Mother